Impact Of Gate Length on Equivalent Circuit Elements In GaAs MESFET Transistors, ISSN / e-ISSN 1682-3427 / 2412-1150 - Benbouza Mohamed Salah; Merabtine Nadjim (Journal of Electron Devices, 2013)
In the information science and technology such as computer science, telecommunications, processing of the signals or images transmission, the field effect components plays a major role. We are interested in this study in Schottky gate gallium arsenide field-effect transistors commonly called GaAs MESFET. In this paper, we mainly present the results of calculating the influence of gate length on input and output impedances of GaAs MESFET Transistors, this physical model is based on the analysis of two-dimensional Poisson equation in the active region under the gate. The theoretical results, based on analytical expressions that we have established, are discussed and compared with those of the simulation.